Variation in the post‐smolt growth pattern of wild one sea‐winter salmon (Salmo salar L.), and its linkage to surface warming in the eastern North Atlantic Ocean. Issue 1 (21st October 2020) - Todd, Christopher D.; Hanson, Nora N.; Boehme, Lars; Revie, Crawford W.; Marques, Ana R.
Abstract: Variation in circulus spacing on the scales of wild Atlantic salmon is indicative of changes in body length growth rate. We analyzed scale circulus spacing during the post‐smolt growth period for adult one sea‐winter salmon ( n = 1947) returning to Scotland over the period 1993–2011. The growth pattern of the scales was subjectively and visually categorized according to the occurrence and zonal sequence of three intercirculus spacing criteria ("Slow", "Fast" and "Check" zones). We applied hierarchical time‐series cluster analysis to the empirical circulus spacing data, followed by post hoc analysis of significant changes in growth patterns within the 20 identified clusters. Temporal changes in growth pattern frequencies showed significant correlation with sea surface temperature anomalies during the early months of the post‐smolt growth season and throughout the Norwegian Sea. Since the turn of the millennium, we observed (a) a marked decrease in the occurrence of continuous Fast growth; (b) increased frequencies of fish showing an extended period of initially Slow growth; and (c) the occurrence of obvious growth Checks or hiatuses. These changes in post‐smolt growth pattern were manifest also in decreases in the mean body length attained by the ocean midwinter, as sea surface temperatures have risen.